Safety and immunogenicity of a modified Omicron-adapted inactivated vaccine in healthy adults: a randomized, double-blind, active-controlled Phase III clinical trial - Hu, Jialei; Liu, Yueyue; Liu, Shuo; Shu, Qun; Yang, Xuenan; Chu, Kai; Qiao, Yaping; Hu, Yaling; Wang, Kaiqin; Pan, Hongxing (Frontiers in Immunology, 2023)
Background Updated vaccine strategies are needed to protect against new SARS-CoV-2 variants with increased immune escape. Here, information on the safety and immunogenicity of an inactivated Omicron-adapted vaccine is presented, as compared with CoronaVac. Methods A randomized, double-blind, active-controlled, phase III clinical trial was conducted to compare a modified Omicron-adapted vaccine (Omicron vaccine) with the authorized prototype vaccine (CoronaVac®) as a booster dose. Healthy adults aged ≥18 years, who have previously received 2 or 3 doses of CoronaVac (2C or 3C cohort) at least 6 months before, were enrolled to get a booster dose of Omicron vaccine or CoronaVac in a ratio of 2:1 (2C/3C+1O/1C). Back-up serums after two initial doses of CoronaVac (2C+0) for adults aged 26-45 years were collected from a previous study. Immunogenicity and safety data at 28 days after vaccination were collected and analyzed. One of the primary objectives was to evaluate the superiority of immunogenicity of Omicron vaccine booster against Omicron BA.1, compared with CoronaVac booster against BA.1. Another objective was to evaluate the non-inferiority of immunogenicity of Omicron vaccine booster against BA.1, compared with two initial doses of CoronaVac against ancestral strain. Results Between June 1st and July 21st, 2022, a total of 1,500 healthy adults were enrolled. Results show that all pre-specified superiority criteria for BA.1 neutralizing antibody were met. Specifically, within the 3C cohort (3C+1O vs. 3C+1C), the geometric mean titers’ (GMT) ratio and 95% confidence interval (CI) was 1.64 (1.42, 1.89), with the lower 95%CI ≥1; a GMT ratio of 1.84 (1.57, 2.16) was observed for 2C+1O versus 3C+1C. For seroconversion rate, the lower 95%CIs of differences between immuno-comparative groups (2/3C+1O vs. 3C+1C) were all above the superiority criterion 0%. However, the non-inferiority criterion of the lower 95%CI of GMT ratio ≥2/3 was unfulfilled for 2C/3C+1O against BA.1 versus 2C+0 against ancestral strain. Safety profiles were similar between groups, with no safety concerns identified. Conclusion The Omicron-adapted vaccine was well-tolerated and could elicit superior immune responses as compared with CoronaVac against Omicron, while it appeared inferior to CoronaVac against ancestral strain. Clinical trial registration https://classic.clinicaltrials.gov/ct2/show/NCT05381350?term=NCT05381350&draw=2&rank=1, identifier NCT05381350.